Breaking the Chains of Male Chauvinism and Celebrating Feminism in Sylvia Plath’s and Kamala Das’ Poetry - Khalid; Farman Ullah; Ubaid Ullah Ubaid; Dr. Sayyed Rashid Ali Shah; Hussain Ahhmad (Al-Qanṭara, 2023)
The present research examines masculine chauvinism, feminism, and how they are portrayed in Sylvia Plath and Kamala Das' poetry. It explores the idea of male supremacy and its negative implications, contrasting them with the feminist movement's support for the autonomy and rights of women. The study reveals the poets' experiences living under the shadow of male domination as it dissects the themes of love, identity, and death in their works. The different reactions of the poets to male chauvinism are studied via a comparative analysis of poems like "Mushroom" and "An Introduction," illustrating their transitions from resistance to final revolt against social conventions. In the setting of male-dominated society, as shown in Plath and Das' poetry, this research illuminates the changing narratives of empowerment and resistance.